2011
DOI: 10.1007/s12640-011-9288-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute Brain Damage Induced by Acetaminophen in Mice: Effect of Diphenyl Diselenide on Oxidative Stress and Mitochondrial Dysfunction

Abstract: Organoselenium compounds exhibit antioxidant activity, as well as a variety of biological activities, with potential pharmacological and therapeutic applications. The aim of this study was to investigate the effect of diphenyl diselenide (PhSe)(2) in reversing oxidative brain damage and mitochondrial dysfunction caused by administration of acetaminophen (APAP) in mice. Mice received a toxic dose of APAP, followed by a dose of (PhSe)(2) 1 h later. Four hours after the administration of APAP, plasma was withdraw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 57 publications
0
37
0
Order By: Relevance
“…Samples of liver mitochondria were incubated in 1 mL of medium containing 10 mM Tris-HCl (pH 7.4), 320 mM mannitol, 8 mM K 2 HPO 4 , 4 mM MgCl 2 , 0.08 mM EDTA, 1 mM EGTA and 0.2 mg/mL BSA (Da Silva et al 2011). Respiration of mitochondria (1 mg of protein/mL was initiated with a cocktail of FAD + -linked substrates at 5 mM (rotenone and succinate) and phosphorylating (state III) respiration was initiated by the addition of 200 nmol of ADP.…”
Section: Mitochondria Respiration Rates and Phosphorylation Efficiencymentioning
confidence: 99%
“…Samples of liver mitochondria were incubated in 1 mL of medium containing 10 mM Tris-HCl (pH 7.4), 320 mM mannitol, 8 mM K 2 HPO 4 , 4 mM MgCl 2 , 0.08 mM EDTA, 1 mM EGTA and 0.2 mg/mL BSA (Da Silva et al 2011). Respiration of mitochondria (1 mg of protein/mL was initiated with a cocktail of FAD + -linked substrates at 5 mM (rotenone and succinate) and phosphorylating (state III) respiration was initiated by the addition of 200 nmol of ADP.…”
Section: Mitochondria Respiration Rates and Phosphorylation Efficiencymentioning
confidence: 99%
“…A previous study (da Silva et al, 2012) reported that brain Na + -K + -ATPase activity in mice is inhibited after acetaminophen treatment, but this inhibitory effect is eliminated by co-treatment with an antioxidant. Thus, inhibition in Na + -K + -ATPase activity is caused by pain relievers indirectly via oxidase stress, lipid peroxidation, and/or free radicals.…”
Section: Effects Of Pain Relievers On Planarian and Shrimp Atpase Actmentioning
confidence: 99%
“…Current knowledge about the toxicity of overdosing pharmaceuticals suggests that acetaminophen exerts its neurotoxicity indirectly by decreasing the GSH level and generating reactive oxygen species (ROS), leading to oxidative stress and influencing the antioxidant capacity of the whole organism, including the brain (Bessems and Vermeulen, 2001;da Silva et al, 2012). Thus, brain damage induced by acetaminophen treatment in mice could be reversed by further treatment of anti-oxidative diphenyl diselenide (PhSe 2 ) (da Silva et al, 2012).…”
Section: Effects Of Pain Relievers On Planarian and Shrimp Mao Activimentioning
confidence: 99%
See 2 more Smart Citations